Custos logísticos e os desafios do transporte e da distribuição no Vale do Paraíba: Estudo de Caso: Fonte MARIAH - Santos Reis, Danilo Frutuoso dos (2025)
According to the National Logistics Plan, the PNL, the Brazilian transport matrix, in 2015 figures, has a high participation of road transport (65%), while the most efficient modes, waterway and rail, both participate with 15%. Asa result, the supply chain in several sectors becomes saturated due, in many cases, to poor road conditions and the high cost of fuel, which directly impacts the logistical cost of distribution. Transport normally represents between one and two thirds of total logistics costs and therefore, increasing efficiency is one of the biggest concerns in the distribution logistics sector. The objective of this work is to analyze the logistical costs related to transportation/distribution and present viable solutions to mitigate these costs. Using exploratory, descriptive, bibliographic and documentary research supported by case studies, it was hoped and achieved that the results produced could contribute to the understanding of the topics covered.